MACHINE LEARNING PREDICTION OF ENDO-PERIO LESIONS USING RADIOGRAPHIC IMAGE - Thiru Kumaran, Jeevitha, Jayalakshmi S (Cuestiones de Fisioterapia, 2023)
The introduction to a machine learning prediction study on endo-perio lesions using radiographic images should outline the significance of the problem, current challenges in diagnosis, and the potential impact of predictive models